2016
DOI: 10.4194/1303-2712-v16_2_11
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two experiments were conducted to evaluate the effects of three water recirculating duration (daytime (07.00h to18.00h); nighttime (18.00h to 07.00h); and 24 hours control) and shading (30%, 60% and no shading control), respectively, on growth and sap's nitrate content of lettuce in a commercial aquaponic system integrated with red tilapia culture. First experiment showed that water recirculating time did not affect the lettuce growth, thus offering the possibility to increase aquaponics profitability by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Studies conducted by [35] show that the variation of water load affects not only energy costs, but also fish and plant yields, as well as the removal of nutrients like phosphorus, nitrates, potassium and the balance of dissolved oxygen at optimal levels for the system. These studies found that at a constant rate of 1.5 l/min, carp (Cyprinus carpio) and spinach (Beta vulgaris) crops showed better growth and weight gain, respectively; Moreover, [36] found similar water flow rates, reporting that at 1.6 l/ min, African catfish (Clarias glariepinus) and water spinach (Ipomoea aquatica) crops gave better performance than at lower flows, as demonstrated in [26], stating that the lower the flow rates, the less capacity the plants have to assimilate nitrogen, phosphorus and potassium.…”
Section: Recirculating Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted by [35] show that the variation of water load affects not only energy costs, but also fish and plant yields, as well as the removal of nutrients like phosphorus, nitrates, potassium and the balance of dissolved oxygen at optimal levels for the system. These studies found that at a constant rate of 1.5 l/min, carp (Cyprinus carpio) and spinach (Beta vulgaris) crops showed better growth and weight gain, respectively; Moreover, [36] found similar water flow rates, reporting that at 1.6 l/ min, African catfish (Clarias glariepinus) and water spinach (Ipomoea aquatica) crops gave better performance than at lower flows, as demonstrated in [26], stating that the lower the flow rates, the less capacity the plants have to assimilate nitrogen, phosphorus and potassium.…”
Section: Recirculating Systemsmentioning
confidence: 99%
“…It is important to highlight the water cycling times, taking into account continuous and intermittent flow cycles, as proven by [35] in a comparative study, using continuous recirculation times of 11, 13 and 24 hours, taking water samples in the effluents of Tilapia (Oreochromis niloticus) (inlet to the hydroponic system) and Lettuce (Lactuca sativa) (throughout the hydroponic system), measuring temperature, dissolved oxygen, conductivity, pH, nitrates, nitrites and ammonium, including plant growth. It was found that it is possible to obtain similar nutrient assimilation in periods of 11 and 13 hours regardless of whether they are performed during the day or night, in contrast, the study by [37] shows that intermittent cycles of 10min on and 50min off in carp (Cyprinus carpio) and mint (Mentha arvensis) crops can maintain temperature and dissolved oxygen balance in water, at the cost of suffering interruptions in the nitrification process and therefore low crop yields.…”
Section: Recirculating Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaponics system (APS) is a modern agricultural technique that provides a more sustainable food production system through a synergistic combination of recirculation aquaculture system (RAS) (Love et al 2015) and hydroponic (HP) (Resh 2012) where the biological processes in the system produce nitrogen (N) in the form of nitrate (NO 3 ) as the main end product (Graber and Junge 2009;Rakocy et al 2006;Rakocy 2012). However, integration tilapia and lettuce being as one of the most significant integrations in APS and the success of this symbiotic plays a crucial role in improving the sustainability of the agriculture production system (Ajitama et al 2018;Jordan et al 2018a;2018b;Sreejariya et al 2016).…”
Section: Introductionmentioning
confidence: 99%